2010
DOI: 10.1007/s10151-009-0554-7
|View full text |Cite
|
Sign up to set email alerts
|

First experiences with pudendal nerve stimulation in fecal incontinence: a technical report

Abstract: Sacral nerve stimulation (SNS) is an established treatment for refractory lower urinary tract and bowel dysfunction. In some urological patients, SNS does not have satisfactory results. Pudendal nerve stimulation (PNS) has recently been proposed for these patients and successfully tested. Given the sometimes unsatisfactory results after SNS in fecal incontinence (FI), we tested PNS on patients suffering from FI. We used the device and implantation technique described by Spinelli et al. By making a slight chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…While it has been studied in the treatment of neurogenic bladder disorders, there are currently no large-scale studies examining its utility for fecal incontinence. 54 In 2012, the LINX esophageal reflux management system, a ring of titanium beads with a magnetic core, was introduced for the treatment of GERD and found to be efficacious and improve patients' quality of life. While the natural inclination is to apply the same concept for fecal incontinence, studies are limited to pilot series, and the method has yet to gain FDA approval.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…While it has been studied in the treatment of neurogenic bladder disorders, there are currently no large-scale studies examining its utility for fecal incontinence. 54 In 2012, the LINX esophageal reflux management system, a ring of titanium beads with a magnetic core, was introduced for the treatment of GERD and found to be efficacious and improve patients' quality of life. While the natural inclination is to apply the same concept for fecal incontinence, studies are limited to pilot series, and the method has yet to gain FDA approval.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Bereits in den 1960er Jahren wurden an Menschen operative Techniken zur Reinnervation des unteren Harntrakts erprobt [3]. Die Arbeitsgruppe um Xiao [30] …”
Section: Neuromodulation Durch Mikrochirurgische Nervenanastomoseunclassified
“…At a median follow up of 59 (30-72) months, ten of these patients became continent. The Cleveland Clinic Florida-FI score improved from 16 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) at baseline to 3 (0-7). Two of these devices were explanted due to infection following revisional surgery.…”
Section: The Prosthetic Anal Sphinctermentioning
confidence: 99%
“…At present, only a few reports have described PNS as a treatment for FI. The first was a two patient case series in 2010 [10]. In 2011 George et al [39] reported its use in seven patients who had had a poor response to SNS.…”
Section: Pudendal Nerve Stimulationmentioning
confidence: 99%
See 1 more Smart Citation